2002
DOI: 10.1073/pnas.132272099
|View full text |Cite
|
Sign up to set email alerts
|

Alternate interactions define the binding of peptides to the MHC molecule IAb

Abstract: T he crystal structures of a variety of MHCI (1-9) and MHCII (10-23) molecules have revealed their features that lead to stable peptide binding. Conserved amino acids of MHCI interact with the N terminus and C terminus of the peptide in virtually all isotypes and alleles. Between these termini, the peptide can vary in length and in the path it takes through the binding groove, often bulging out of the groove in the middle. In MHCII, the N and C termini of the peptide generally extend beyond the binding groove … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 55 publications
4
77
0
Order By: Relevance
“…Peptides were eluted from these preparations and subjected to MS or MS-MS analysis as previously reported (32) and as described in Materials and Methods. A preliminary MS-MS analysis of the peptides isolated from WT and mutant I-A b showed that they had I-A bbinding motifs (Table S2) (33,34). This finding served to validate our method of peptide isolation and suggested that the I-A b mutations did not affect the I-A b peptide-binding motif.…”
Section: Mutations Of the I-a B Conserved Amino Acids Affect The Presmentioning
confidence: 58%
“…Peptides were eluted from these preparations and subjected to MS or MS-MS analysis as previously reported (32) and as described in Materials and Methods. A preliminary MS-MS analysis of the peptides isolated from WT and mutant I-A b showed that they had I-A bbinding motifs (Table S2) (33,34). This finding served to validate our method of peptide isolation and suggested that the I-A b mutations did not affect the I-A b peptide-binding motif.…”
Section: Mutations Of the I-a B Conserved Amino Acids Affect The Presmentioning
confidence: 58%
“…Several MHC class II molecules (I-A d , I-A k , I-A u , I-A b , and I-A g7 ) (19,20,42,43,45) do have a hydrogen bond between glutamate ␤74 and the P5 amide. The side chain of alanine ␤74 in DQ2 is, however, not a hydrogen bond acceptor.…”
Section: Discussionmentioning
confidence: 99%
“…MOG37-52 being the optimal minimal stimulatory sequence for 95% of the MOG35-55 T cell clones, it was conceivable that any potential core epitope would be contained within it. Nonameric registers within MOG37-52 with potential binding affinity to I-A b were analyzed by modeling the interaction of MOG37-52 with I-A b , based on the recently available I-A b crystal structure [21]. The modeling data for the MOG37-52/I-A b interaction (Fig.…”
Section: Diverse Tcr V Gene Usage By Mog35-55-specific T Cell Clonesmentioning
confidence: 99%
“…The model of the MOG37-52/A b interaction with MOG40-48 as the core epitope (Fig. 1A) positioned residues R41, S42, F44, R46 and V47 in pockets p2, p3, p5, p7 and p8, respectively, as potential TCR interacting residues, with residues MOG41R and MOG44F in p2 and p5 predicted to be the more crucial according to the available structure of the TCR-MHC class II-peptide complex [21]. These predictions were recently corroborated experimentally [26,27].…”
Section: Mog37-52-reactive Clones Expressing Highly Heterogeneous Tcrmentioning
confidence: 99%
See 1 more Smart Citation